Excess Volumes of Binary Liquid Mixtures of Benzene and Carbon Tetrachloride with Cumene and Pseudocumene - Yadav, K.; Kumari, Anita; Kumar, M. (Asian Journal of Chemistry, 2012)
Densitites (r), visocisities (h) and ultrasonic velocities for binary liquid mixtures formed from benzene and carbon tetrachloride with cumene and psedocumene have been measured at two different temperatures 303.15 and 293.15 K. Excess volume of mixing (nE), deviation of excess volume (DnE) from ideal mole fraction law and parameter (d) as a measure of strengh of interaction between components of binary mixtures have been calculated from the data of densities and viscosities. Excess volumes have been found to be negative and positive in sign for binary mixtrue of carbon tetrachloride with cumene and pseudocumene and carbon tetrachloride with benzene at entire mole-fraction range and at both temperatures 303.15 and 293.15 K. On the other hand, Dh were found to be negative for binary mixtures of carbon tetrachloride with cumene and pseudocumene except the binary mixture of carbon tetrachloride with benzene at entire mole fraction range and temperatures mentioned. Positive value of excess volumes for three mixtures (carbon tetrachloride with benzene, cumene and pseudocumene) show weak molecular interactions between components. However, the negative value of Dh for binary mixtures of carbon tetrachloride with cumene and pseudocunene show weak interactions between components. The experimental values of excess volumes of mixing (nE) have been analyzed in the light of Flory’s theory.